Effects of Culture Supernatants of Peripheral Blood Leukocytes on Bone-minerals Resorbing Activity by Human Monocytes - SATO, Iwao; IWAKAWA, Yoshinobu; NAKAMURA, Yasutaka; MARUMOTO, Yoshiko; NISHIMOTO, Masazumi; FUJIHASHI, Hiroshi; IKEDA, Katsumi (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1985)
It has been reported that human peripheral blood monocytes in vitro release calcium from fetal rat calvaria and from synthetic hydroxyapatite (HA) (SATO et al., 1984). In this paper, we examined the effects of lymphokine on the release of calcium from HA by human monocytes. Peripheral blood was collected from patients with periodontal disease (PPD) and from clinically healthy individuals, and peripheral blood leukocytes (PBL) were isolated by differential centrifugation using Sodium metrizoate-Ficoll. Then the monocytes were separated by the method based on adherence to plastic. PBL were cultured with phytohemagglutinin or dental plaque and afterwards culture supernatants (PBL-sup) were separated and used as a source of lymphokines (Osteoclast-activating factor: OAF and others). Assay of calcium from HA was done as follows: PBL supernatants were to a mixed suspension of monocytes and HA mixed cultured in 5% CO2 at 37°C for 24 to 72 hours. The quantity of released calcium from HA was measured by atomic absorption analysis. Human monocytes induced the release of calcium from HA, and its level was increased more significantly by addition of PBL supernatants from PPD than from healthy subjects. And Nitro Blue Tetrazorium reduction activity and [3H] Thymidine incorporation activity of monocytes were increased too by addition of PBL-sup. These results suggest that bone resorption activity of human monocytes is activated by lymphokines, perhaps by what is called “OAF”.